Defining the role of facilitated mediation in medical treatment decision-making for critically ill children in the Australian clinical context. (June 2023) - Preisz, Anne; Bhatia, Neera; Michalson, Patsi
In this article, we explore alternative conflict resolution strategies to assist families and clinicians in cases of intractable dissent in paediatric health care decision-making. We focus on the ethical and legal landscape using cases from the Australian jurisdiction in New South Wales, while referencing some global sentinel cases. We highlight a range of alternative means of addressing conflict, including clinical ethics support, and contrast and contextualise facilitative or interest-based mediation, concluding that legal intervention via the courts can be protracted and distressing and should be a 'last resort'. We acknowledge many might view this as the current status quo, but we go further to recommend strategies optimal for all parties to recognise early signs of conflict and prevent its harmful escalation. While more empirical research is needed, we contend that interest-based mediation may be a valuable adjunctive method of conflict resolution. If judiciously distinguished from and utilised with clinical ethical support, it can be an effective tool to address dissent and its negative sequelae in paediatric healthcare decision-making.